A randomized controlled trial of resistance and endurance exercise in amyotrophic lateral sclerosis. Issue 3 (3rd April 2018) - Clawson, Lora L.; Cudkowicz, Merit; Krivickas, Lisa; Brooks, Benjamin R.; Sanjak, Mohammed; Allred, Peggy; Atassi, Nazem; Swartz, Amy; Steinhorn, Gabrielle; Uchil, Alpa; Riley, Kristen M.; Yu, Hong; et al.
Abstract: Objective: Evaluate the safety and tolerability of resistance and endurance exercise in ALS participants as measured by their ability to complete this six-month study. Methods: Participants were randomized to Resistance, Endurance, or Stretching/Range of Motion (SROM the exercise regimen prescribed for most ALS patients) exercises. All exercises were performed at home with an individualized regimen designed by a physical therapist trained in ALS management. Primary outcome measures were tolerability of the exercises at 24 weeks defined by 50% of participants completing at least 50% of the prescribed exercise regimen. Secondary outcome measures included the ALSFRS-R, pulmonary FVC, and other measures of ALS function. Results: At 12 and 24 weeks, all three exercise regimens were tolerated according to our pre-specified criteria. Compliance to the prescribed exercise regimen was the highest in the resistance and SROM arms of the study. All three forms of exercise were considered safe as there were no differences in the rates of disease progression among groups. There were no differences in the secondary outcome measures and feasibility for evaluating these measures was successful. In a post-hoc analysis, there was a trend towards fewer falls in the Resistance and Endurance groups. Conclusions: This study demonstrates that SROM, resistance, and endurance exercise are all safe to be performed with the specified regimen without any worsening of outcomes as related to ALS function. All three forms of exercise were tolerated with resistance and SROM exercises showing the highest compliance over the 24 week-period.